Non-syndromic multiple keratocyst odontogenic tumor: A rare case report - Abhijeet Alok; Sunil R Panat; Indra Deo Singh; Shivani Singh (Wolters Kluwer Medknow Publications, 2015)
Keratocystic odontogenic tumors (KCOTs) are one of the most frequent features of nevoid basal cell carcinoma syndrome (NBCCS). The condition is linked with mutation in the PTCH gene. Partial expression of the gene may result in occurrence of multiple recurring odontogenic keratocysts (OKCs). Although KCOTs are common in clinical practice, simultaneous occurrence of multiple cysts in both the maxilla and mandible of a patient is rare. These patients have early propensity to develop multiple neoplasms like basal cell carcinoma and medulloblastoma. Hence, early diagnosis and treatment is of utmost importance in reducing the severity of the long-term sequelae of NBCCS. We report a rare case of multiple KCOTs in a non-syndromic male patient, with emphasis on its diagnosis, radiographic features, and treatment.